THE NECESSITY OF ELABORATING CURRICULAR STANDARDS OF PERFORMANCE IN THE "THEORETICAL SPORTS TRAINING" DISCIPLINE - Mariana Juravle (Editura Univeristatii "Stefan cel Mare" din Suceava, 2018)
The criteria of evaluation of the quality of the teachinglearning product are the curricular standards. For the growth of the objectivity and the precision of the evaluation, elaborating curricular standards of performance in the "Theoretical sports training" discipline has become a necessity because, up to the present day, no official document has been conceived for this purpose (as it happens for the majority of the disciplines). The elaboration of these standards is absolutely necessary as it provides a connection between curriculum and evaluation, and levels of performance are determined on their behalf as well as the descriptors of performance and the instruments of evaluation which are elaborated.